A educação eugenista latino-americana: correspondências entre os intelectuais brasileiros e argentinos nas décadas de 1920-1930 - Roitberg, Guilherme Prado (Diálogos Latinoamericanos, 2021)
The science of racial improvement or eugenics was created in the late 19th century by Francis Galton. Based on social Darwinism, this science became popular among the influential Latin American intellectual elite, leading to the creation of organizations committed to the racial improvement of the population through sanitary medicine and combating the “degenerative threats” represented by black, mestizos, foreigners and handicapped people. Supported by historical perspective, the article investigate the utopian-racial project of the eugenic movement in Latin America during the years 1920 to 1930. Through a documentary research of publications by Brazilian and Argentine eugenicists, the article seeks to understand the vicissitudes of the intellectual field that allowed the development of Latin American scientific racism through the institutionalization of eugenic education. In dialogue with the specialized bibliography, it is demonstrated how these documents are fundamental sources in understanding of Brazil-Argentina connection envisioned by the eugenic movement, as well as the permanency of this intellectual support network during the 20th century.